Some preliminary evidence on the short-run aggregate demand effects of fiscal policy - Canlas, Dante B. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1986)
The crowding out of private consumption by fiscal policy is examined using a short-run consumption function. There is evidence of a one-for-one crowding out of consumption by government purchases of goods and services. The effects of debt financing on consumption are mixed. Internal debt exerts a negative effect while external debt, a positive one.